POTENSI PENGEMBANGAN KOMUNITAS SOSIAL BUDAYA ASEAN DAN KEMUNGKINAN PERAN KONSTRUKTIF ASEAN: SEBUAH KAJIAN KUALITATIF - Sundrijo, Dwi Ardhanariswari; Marthinus, Pierre (UI Scholars Hub, 2010)
The article discusses the ongoing development of the ASEAN Socio-Cultural Community. Literature study as well as in-depth interviews of key stakeholders representing Indonesian government, civil society, and academics is utilized to identify its potential leverage, inherent problematics, as well as possible constructive action that can be taken by Indonesia to support and strengthen the ASEAN Socio-Cultural Community. The socio cultural pillar's importance stems from its potential leverage to increase civil society participation, encourage tripartite state-market-civil society cooperation, and construct a cohesive regional identity. Inherent problematics of the ASEAN Socio-Cultural Community includes the leadership's weak commitment from the Philippines, lack of political will from member states, civil society's characteristics, complexities of socio cultural issues, as well as the ASEAN Socio-Cultural Community's characteristics in comparison to the ASEAN Political Community and the ASEAN Economic Community. Strengthening measures identified are (1) pillar empowerment through prioritizing issues with greater regional leverage overlapping with the political-security and economic pillar and socialization to increase society's awareness and participation, as well as (2) empowerment of key stakeholders including governmental agencies, civil society, and the ASEAN institution. Constructive action recommended includes encouraging increased leadership within the community, initiating a corrective internal mechanism, awareness raising, and